Pentingnya Pendampingan Orangtua Dalam Meningkatkan Motivasi Belajar Dari Rumah Di Masa Pandemi Covid-19 Untuk Anak Usia 10-12 Tahun Di Dusun Sentagi - Muriana Muriana; Saenom Saenom; Felipus Nubatonis; Marthen Mau (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Education is a process of educating individuals to achieve certain goals in the form of positive change. Children need guidance and supervision from parents because children's lives are the parents' responsibility. However, the fact is that in general some parents pay little attention to their children's learning because they are busy with their work and lack of supporting learning facilities. This research aims to determine the importance of parental assistance in increasing motivation to study from home during the Covid-19 pandemic for children aged 10-12 years in Sentagi hamlet. The research methods used are qualitative, observation, interviews, documentation and literature study. The results of the research obtained are that children aged 10-12 years when studying during the Covid-19 pandemic really need parental assistance, so that the online learning process can run smoothly. The need for optimal parental assistance is because children were sent home when Covid-19 hit the world, including Indonesia. So, parents are increasingly providing assistance to their children aged 10-12 years in participating in the online learning process, so the learning process will run smoothly because the teachers teach online, including giving assignments to be done online too.